Prosaptia Contigua C. Presl (Grammitidaceae), a New Record for Vietnam - Toan, Nguyen Cong; Loc, Phan Ke; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2DO - 10.25073/2588-1140/vnunst.4863, 2019)
Abstract: The specimens of genus Prosaptia C. Presl (family Grammitidaceae) stored in the Herbarium of the University of Science under Vietnam National University were studied with the traditional morphological methods. The study provides descriptions, illustrations and comparisons of 6 species of genus Prosaptia, namely P. alata, P. barathrophylla, P. intermedia, P. pectinata, P. obliquata and P. contigua . Prosaptia contigua (G.Forst.) C.Presl has been identified as a new record for the flora of Vietnam. Keywords : Genus Prosaptia, Prosaptia contigua, Grammitidaceae, new record for the flora of Vietnam. References:   [1] M.L. Tardieu-Blot and C. Christensen, Prosaptia C. Presl., In F. Gagnepain, Flore Générale De L'Indo-Chine Tome 7, Part. 2, Fasc.9, Masson et CieÉditeurs, Paris, 1941, pp.528-531. [2] P.H. Hộ, Cây cỏ Việt Nam, An Illustrated Flora of Vietnam, Quyển I, Tập 1, Montréal, published by the author, 1991, pp.139. [3] P.K. Loc, The Updated Checklist of the Fern Flora of Vietnam following the classification scheme of A. Smith et al., (2006), Fairylake Botanical Garden 9 (3) (2010) 1-13. [4] B.S. Parris, W.C. Cheng, C.H. Tian, L.T. Ngan, N.Q. Dat, and L.H. Truong, New species and records of grammitid ferns (Polypodiaceae) for Vietnam, Phytotaxa 266 (1) (2015) 39. http://doi.org/10.11646/phytotaxa [5] C.L. Blume, Davallia alata, Enumeratio Plantarum Javae 2, Apud J.W. van Leeuwen, Lugduni Batavorum (Leiden), 1928, pp. 230. [6] B.S. Parris, 40. Grammitidaceae - 7. Prosaptia. In B.S. Parris, R. Kiew, R.C.K. Chung, L.G. Saw & E. Seopadmo eds, Flora of Peninsular Malaysia, Ser. I. Ferns and Lycophytes, Malaysia 1 (2010) 170-182. [7] J.G. Baker, Polypodium barathrophyllum J. Bot. 29 (1891)107-108. [8] S.J. Moore and B.S. Parris Prosaptia, In Z.Y Wu, P.H. Raven and D.Y. Hong, eds. Flora of China, Vol. 2-3 (Pteridophytes), Science Press (Beijing) & Missouri Botanical Garden Press (St. Louis), 2013, pp. 846-848. [9] C.L. Blume, Polypodium obliquatum, Enumeratio Plantarum Javae fasc., 2, J.W. Apud van Leeuwen, Lugduni Batavorum (Leiden), 1828, pp.128. [10] http://rbg-web2.rbge.org.uk/thaiferns/factsheets/ index.php?q=Prosaptia_alata.xml [11] http://bioportal.naturalis.nl/ [12] http://www.nhm.ac.uk/ [13] https://www.gbif.org/occurrence/1697870613 [14] C.H. Tian, C.H. Hsin, Y.L. Chien, L.C. Wen, M.H. Yao and H.C. Yi, New Additions to the Fern Flora of Taiwan (3), Taiwan J For Sci 30 (2) (2015) 135. https://doi.org/ 10.4103/UROS.UROS_142_18